THE CORRELATION BETWEEN ENGLISH READING ALOUD AND ENGLISH READING COMPREHENSION AT THE NINTH GRADER OF SMPN 192 JAKARTA - Rika Virtianti; Ria Yuliasari (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This research is conducted to measure whether there is a correlation between English reading aloud and English reading comprehension. It consists of two variables namely; English reading aloud as independent variable and English reading comprehension as dependent variable. The population of this research is the students of SMP N 192 Jakarta that consist of 60 students and divided into two classes and the method that is used is simple random sampling, with the sample consist of 30 students. The method that is used in this research is survey. It means that, the research use oral test for reading aloud and multiple choice tests for reading comprehension. Then, all of answers which are got by researcher are noted, processed and analyzed. The oral test is related to the theme above that is used for getting information of population. In this research, first of all the researcher tests the population through reading English text loudly to know the students’ reading aloud score. Then, researcher gives multiple choice tests to know student’s reading comprehension.